Anxiety 101/ by Moshe Matthews and Gerald Matthews - "Zeidner, Moshe" (New York, 2011)
Anxiety refers to a state in which an individual is inordinately apprehensive, tense, and uneasy about the prospect of something terrible happening. Anxiety becomes a source of clinical concern once it begins to interfere with the ability to function in daily life. Anxiety 101 presents a state-of-the-art review of modern theories, research findings, assessments, and remediation relevant to the study of anxiety. This quick, user-friendly book is designed to address the most critical aspects of anxiety, especially those involving individual differences and interventions. To offer comprehensive coverage of anxiety, the authors present the best of the new research drawing from differential psychology, personality and social psychology, stress, coping, psychobiology, and neuroscience. The Psych 101 Series: Short, reader-friendly introductions to cutting-edge topics in psychology. With key concepts, controversial topics, and fascinating accounts of up-to-the-minute research, The Psych 101 Series is a valuable resource for all students of psychology and anyone interested in the field.
Keywords: Anxiety